Rhino-Orbital Mucormycosis in a COVID-19 Patient: A Dreadful Challenge - Dhakal, A.; Pokharel, M.; Madhup, S.; Khadka, L.; Sapkota, B. (Kathmandu University Medical Journal, 2022)
Coronavirus disease 2019 (COVID-19) is a pandemic disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2). COVID-19 infections may be associated with a wide range of bacterial and fungal co-infections. Recent studies are reporting invasive fungal infection associated with severe COVID-19. Herein, we report a case of COVID-19 rhino-orbital mucormycosis infection caused by Rhizopus sps in a 32 year old diabetic patient who was successfully managed with early aggressive debridement of infected tissue endoscopically with extended ethmoidectomy by modified Denker’s approach along with orbital decompression and antifungal therapy with Liposomal Amphotericin B and Posaconazole. Serial diagnostic nasal endoscopy showed no evidence of progression of the infection. The patient was discharged on 21st day of hospitalization still on oral Posaconazole for a total of 3 months.